(3TQM GdCQLhRI GdWHjIs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdefYe dMjGI GdfahS aEfg PcQJ HGdeLdS GdYGdi GdCQLhRI GdefShHI Edi GHf SjfG ai GdWH s
(3BNQgG (B:s
(3Ke jdRe UGMHg JTcjf Pdc GdYVh dG Cbd ef TgQ hQHeG GMJjL Edi Cf jHbi YTQkG HYO GdTgQ CYfi CQHYjf jhekG hgPG GfbVGA Gdbhd ai TQM gPg GdCQLhRI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B63s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs